HUBUNGAN GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI DENGAN KINERJA TENAGA ADMINISTRASI SEKOLAH - Niqma Chelia Paramudityas; Ibrahim Bafadal; Ahmad Nurabadi (Universitas Negeri Malang, 2019)
Abstract: The purpose of this research is to find: (1) the principal’s leadership style at vocational high school in city of Malang; (2) organizational culture at vocational high school in city of Malang; (3) level of performance of the school administration staff at vocational high school in city of Malang; (4) relationship between the principal’s leadership style the most dominant with organizational culture the most dominant at vocational high school in city of Malang; (5) relationship between the principal’s leadership style the most dominant with performance of the school administration staff at vocational high school in city of Malang; (6) relationship between organizational culture the most dominant with performance of the school administration staff at vocational high school in city of Malang; and (7) relationship between the principal’s leadership style the most dominant and organizational culture the most dominant with performance of the school administration staff at vocational high school in city of Malang. This research used a correlation quantitave approach. The population in this research were 300 school administration staff. The sampling technique used proportional random sampling and simple random sampling get 171 respondents. Data analysis used descriptive techniques, correlation Product Moment Pearson techniques, and multiple correlation techniques. The results of this research indicated: (1) the principal’s leadership style at vocational high school in city of Malang is participation leadership style in high level; (2) organizational culture at vocational high school in city of Malang is people’s orientation in condusive level; (3) level of performance of the school administration staff at vocational high school in city of Malang in very high level; (4) there is no relationship between the principal’s leadership style the most dominant with organizational culture the most dominant at vocational high school in city of Malang; (5) there is a relationship between the principal’s leadership style the most dominant with performance of the school administration staff at vocational high school in city of Malang; (6) there is a relationship between organizational culture the most dominant with performance of the school administration staff at vocational high school in city of Malang; and (7) there is relationship between the principal’s leadership style the most dominant and organizational culture the most dominant with performance of the school administration staff at vocational high school in city of Malang.Keywords: the principal’s leadership style, organizational culture, performance of the school administration staff Abstrak: Tujuan penelitian ini untuk mengetahui: (1) gaya kepemimpinan kepala sekolah di SMK Negeri se-Kota Malang; (2) budaya organisasi di SMK Negeri se-Kota Malang; (3) tingkat kinerja Tenaga Administrasi Sekolah di SMK Negeri se-Kota Malang; (4) hubungan antara gaya kepemimpinan kepala sekolah yang paling dominan dengan budaya organisasi yang paling dominan di SMK Negeri se-Kota Malang; (5) hubungan antara gaya kepemimpinana kepala sekolah yang paling dominan dengan kinerja Tenaga Administrasi Sekolah di SMK Negeri se-Kota Malang; (6) hubungan antara budaya organisasi yang paling dominan dengan kinerja Tenaga Administrasi Sekolah di SMK Negeri se-Kota Malang; dan (7) hubungan antara gaya kepemimpinan kepala sekolah yang paling dominan dan budaya organisasi yang paling dominan dengan kinerja Tenaga Administrasi Sekolah di SMK Negeri se-Kota Malang. Penelitian ini menggunakan pendekatan kuantitatif korelasional. Populasi dalam penelitian ini sebanyak 300 Tenaga Administrasi Sekolah. Teknik sampling menggunakan proportional random sampling dan simple random sampling sebanyak 171 responden. Analisis data menggunakan teknik deskriptif, teknik korelasi Product Moment Pearson, dan teknik korelasi ganda. Hasil penelitian ini menunjukkan: (1) gaya kepemimpinan kepala sekolah yang paling dominan di SMK Negeri se-Kota Malang adalah gaya kepemimpinan partisipasi yang tergolong tinggi; (2) budaya organisasi yang paling dominan di SMK Negeri se-Kota Malang adalah orientasi orang yang tergolong kondusif; (3) tingkat kinerja tenaga administrasi sekolah di SMK Negeri se-Kota Malang tergolong sangat tinggi; (4) tidak terdapat hubungan antara gaya kepemimpinan kepala sekolah yang paling dominan dan budaya organisasi yang paling dominan di SMK Negeri se-Kota Malang; (5) terdapat hubungan antara gaya kepemimpinan kepala sekolah yang paling dominan dan kinerja tenaga administrasi sekolah di SMK Negeri se-Kota Malang; (6) terdapat hubungan antara budaya organisasi yang paling dominan dan kinerja tenaga administrasi sekolah di SMK Negeri se-Kota Malang; dan (7) terdapat hubungan gaya kepemimpinan kepala sekolah yang paling dominan dan budaya organisasi yang paling dominan dengan kinerja tenaga administrasi sekolah di SMK Negeri se-Kota Malang.Kata Kunci: gaya kepemimpinan kepala sekolah, budaya organisasi, kinerja tenaga administrasi sekolah